Preliminary comments on the Brazilian agreement of no criminal prosecution: from its unconstitutionality to its argumentative inconsistency - Andrade, Mauro Fonseca (Revista da Faculdade de Direito da Universidade Federal do Rio Grande do Sul, 2018)
Recentemente, o Conselho Nacional do Ministério Público publicou a Resolução nº 181, de 07 de agosto de 2017, onde apresentou uma nova regulamentação para a investigação criminal presidida pelo acusador público brasileiro. Dentre as novéis disposições lá presentes, o que vem chamando muito a atenção dos operadores do direito é o denominado acordo de não-persecução penal, que se constitui em um acordo de não oferecimento da acusação pelo Ministério Público, dependente do cumprimento das condições firmadas pela pessoa investigada e seu defensor. Em razão disso, o objetivo do presente estudo é analisar a viabilidade dos argumentos apresentados pelo Conselho Nacional do Ministério Público para inserir esse instituto em nosso país. Em um primeiro momento, será analisado o parâmetro internacional utilizado, de modo a observar se é correta a equiparação entre a realidade alemã e a realidade brasileira. Ao depois, será averiguada a correção do argumento sistêmico invocado. Por fim, será averiguada a conformidade constitucional do acordo presente naquela resolução. A título de conclusão, apontarse- á a inconstitucionalidade do acordo de não- persecução penal, e sua incompatibilidade com os argumentos apresentados pelo próprio Conselho Nacional do Ministério Público.On August 7 th 2017, the Brazilian Prosecutor’s National Council published its Resolution 181, which introduced a new regulation to the criminal investigations led by Prosecutors in Brazil. Among all dispositions presented in this new act, there is a special novelty: the possibility of an agreement of no criminal prosecution between prosecutors and defendants assisted by their lawyers. If it is celebrated, the defendants will need to accomplish the conditions imposed and, as a final benefit, they will not be charged and sentenced for the crime committed. As it is a novelty, it is very important that the Law academics and professionals pay close attention to it. Because of it, this study aims to analyze whether the creation of this deal from a Brazilian Prosecutor’s National Council’s act is correct according to the Brazilian law. For this, it will verify if the German agreement’s origin may be used as a reason to create an informal agreement in Brazil. After that, it will analyze if the systemic argument used by the Council helps this innovation. Finally, it will check whether the agreement is constitutionally suitable. In conclusion, it will be possible to claim the Brazilian agreement of no criminal prosecution is unconstitutional and that the Brazilian Prosecutor’s National Council presented inconsistent bases to its creation with no Legislative act